The effect of Citrullus colocynthis (L.) Schrad. fruit on oxidative stress parameters in type II diabetic patients - H Fallah Huseini; A Zaree; R Heshmat; B Larijani; H Fakhrzadeh; R Rezaii Sharifabadi; GA Naderi; J Zaringhalam; AH Shikh Samani (Institue of Medicinal Plants, ACECR, 2006)
Background and Aims: Increased production of oxidative stress intamediates in chronic diabetic patients has been reported in several studies. A close relation between the treatment of diabetes and intensity intermediates of oxidative stress has been demonstrated.   Aim: In the present study effects of Citrullus colocynthis fruit on oxidative stress intermediates in type II diabetic patients is investigated.   Materials and Methods: 44 male and female type II diabetic patients were randomly allocated in two groups of 22 patients each. One group received 100 mg Citrullus colocynthis capsule and the other group received placebo 3 times a day plus standard therapy. The biochemical parameters such as glycosylated hemoglobin (HbA1c), fasting blood glucose, levels as well as oxidative parameters such as glutathione, superoxid dismutase, catalase and malondialdehyde were determined at the beginning and the end of the study after two months.   Results: Result indicated a significant decrease in HbA1c and fasting blood glucose level in Citrullus colocynthis fruit treated patients after two months as compared to beginning of the treatment and also as compare to placebo group. The oxidative stress indicators such as glutathione, superoxid dismotase, catalase and malondialdehyde were not changed significantly in either group after two months of treatment. Conclusion: In type II diabetic patients Citrullus colocynthis fruit treatment improved glycemic profile but did not affect oxidative stress parameters.